(untitled) - Prof. Dr. Peter-Alexis Albrecht, Prof. Dr. Stefan Braum, Prof. Dr. Roland Broemel, Prof. Dr. Thomas Duve, Prof. Dr. Klaus Günther, PräsEuG Marc Jaeger, Président de la Cour de Cassation Vincent Lamanda, Prof. Dr. Guido Pfeifer, RiEuGH Dean Spielmann, Prof. Dr. Tobias Tröger, Prof Dr. Miloš Vec, PräsBVerfG Prof. Dr. Andreas Voßkuhle, Prof. Dr. Astrid Wallrabenstein, Prof. Dr. Dres. h.c. Manfred Weiss (KritV Kritische Vierteljahresschrift für Gesetzgebung und Rechtswissenschaft, 2023)
The CritQ provides a forum for open, interdisciplinary-oriented, intradisciplinary-informed critical jurisprudence grounded in the theory-praxis dialogue. As a European law journal the CritQ reflects the required legal adjustments towards societal, political, and systemic directives in Europe. The list of editors that counts the law schools of the University of Luxembourg and Goethe-University Frankfurt am Main among them, has been prominently enhanced with pioneers of European jurisdiction (Marc Jaeger, Vincent Lamanda, Dean Spielmann, Sir John Thomas, Andreas Voßkuhle). The European public is conveyed by language, thus the CritQ presents articles in German, English, and French.